If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 62 = -6x + 34 Reorder the terms: 62 + -10x = -6x + 34 Reorder the terms: 62 + -10x = 34 + -6x Solving 62 + -10x = 34 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 62 + -10x + 6x = 34 + -6x + 6x Combine like terms: -10x + 6x = -4x 62 + -4x = 34 + -6x + 6x Combine like terms: -6x + 6x = 0 62 + -4x = 34 + 0 62 + -4x = 34 Add '-62' to each side of the equation. 62 + -62 + -4x = 34 + -62 Combine like terms: 62 + -62 = 0 0 + -4x = 34 + -62 -4x = 34 + -62 Combine like terms: 34 + -62 = -28 -4x = -28 Divide each side by '-4'. x = 7 Simplifying x = 7
| 4x^2+43x+70=0 | | 5/n+1=6/n+5 | | x=.3x+8 | | .18x+16=4+.54x | | 3x^2-4x+7=x^2+15x | | 6/2=p-6/p-2 | | 9/m+3=2/4 | | 0=4x^4-18x^3+34x^2-72x+72 | | -28-(-130)= | | 8-7n+5n=44-86 | | 1.5(b+2)+15(2b-9)+b=90 | | 8x+6x-88=66-8x | | 6x=9x-5 | | 10/5=6/k-9 | | 27+w=35 | | -4z^2+6z+1=0 | | 3x(x-6)=6x-90 | | -12x+14=-6x+8 | | 4/2=x/7 | | 9(c-4)+5=3+c-34 | | m/8=10/2 | | 4y=x^2+4x | | -9=-8(1+6y)-1 | | 8f=7f+-3 | | 3/6=p-6/p-4 | | (10x-9)-(-x^2+22x)= | | -3x^2=8-10x | | 12(a-9)=-7-5 | | 3lnx-2ln(5-x)=0 | | 20x+4y=-60 | | 2.5x+3=y | | 0.074*n=74 |